2017
DOI: 10.3390/toxics5020010
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Wastewater Effluent—Source of Contaminants of Emerging Concern: Phytotoxicity of Metronidazole to Soybean (Glycine max)

Abstract: Industrial discharge of active pharmaceutical ingredients (APIs) into the environment in some middle- and low-income countries is not sufficiently regulated. The phytotoxicity of metronidazole (FLAGYL)—one of the most commonly used over the counter (OTC) antibiotics, to soybean (Glycine max) is investigated. Relative growth rate (RGR) expressed in gram per gram per day (gg−1d−1) was applied to plants destructively harvested at maturity (42 d), to determine the toxicological impact. Differences between mean RGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 38 publications
0
9
0
3
Order By: Relevance
“…The mass balance of metronidazole in the solution and adsorbent were derived to get the adsorption variable. The variable was used to evaluate the adsorption parameter of Equation 3and Equation (4). The mass balance derivative of metronidazole for the batch system was written as Equation (5).…”
Section: Pore Structure Of Carbon Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass balance of metronidazole in the solution and adsorbent were derived to get the adsorption variable. The variable was used to evaluate the adsorption parameter of Equation 3and Equation (4). The mass balance derivative of metronidazole for the batch system was written as Equation (5).…”
Section: Pore Structure Of Carbon Materialsmentioning
confidence: 99%
“…Studies showed that pharmaceutical compounds in an aquatic system could have serious effects such as antibiotic-resistant microbes [1], the change of fish reproduction [2], and inhibition of photosynthesis in aquatic organisms [3]. When a waterbody containing antibiotics flows to agriculture land, this could affect the maturity of plants [4]. One of the main sources of pharmaceutical effluents is hospitals which, in Europe, typically discharges pharmaceutical components in the range concentrations of 0.2-11 µg L −1 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Water is a natural resource whose availability depends on its quantity and quality. In freshwater's availability evaluation, it is pivotal to know the pollutant loads, topical and diffuse ones [18,19]. In the last decades, surface water contamination has drastically increased mainly due to anthropogenic emissions of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Os efluentes de indústrias bioquímico-farmacêuticas são provenientes de 5 atividades básicas: A) Pesquisa e desenvolvimento, B) Síntese química e bioquímica, C) Extração de produtos naturais, D) Fermentação e E) Preparação e dosagem de medicamentos (BREMS;LAPKIN;BAEYENS, 2013;DE OLIVEIRA JUNIOR, 2013;JAMES et al, 2014;LARSSON, 2014;YAKUBU, 2017). Os efluentes de indústrias bioquímico-farmacêuticas conterão, principalmente, resíduos dos fármacos que são por elas produzidos, além de subprodutos das reações de síntese e resíduos de todos os reagentes, solventes e catalisadores utilizados no processo.…”
Section: Efluentes De Indústrias Bioquímico-farmacêuticasunclassified
“…As indústrias bioquímico-farmacêuticas geram efluentes complexos e o seu tratamento não pode ser generalizado para todos os efluentes (GOHARY;ELELA;ALY, 1995;VENKATARAMANI, 1995;GULMEZ et al, 1998;KABDASLI;GUREL;TUNAY, 1999;RADJENOVIC;PETROVIC;BARCELO, 2007;DESCHAMPS et al, 2012;DE OLIVEIRA JUNIOR et al, 2013;YAKUBU, 2017).…”
Section: Tratamento De Efluentes De Indústrias Bioquímico-farmacêuticasunclassified